An Observational Study of the Frequency and Pattern of Use of Epidural Steroid Injection in 25, 479 Patients With Spinal and Radicular Pain. Issue 1 (1st January 2001) - Fanciullo, Gilbert J.; Hanscom, Brett; Seville, Janette; Ball, Perry A.; Rose, Robert J.
Abstract : Background and Objectives: Frequency of epidural steroid injections (ESI) and characteristics of patients receiving them are unknown or poorly described. Patients believed to respond better to ESI include young or middle-aged individuals, those with recent onset or a radicular pattern of pain, and patients without previous spinal surgery. The aim of this study is to estimate the frequency of ESI, to examine the characteristics of patients who have them recommended, and to determine if clinical practice reflects published data pertaining to indications for ESI. Methods: Descriptive data from 25, 479 selected patients with spinal and radicular pain were reviewed. Patients were grouped according to whether or not ESI was recommended, scheduled, prescribed, or continued. Prevalence of ESI use and patient characteristics were compared using standard statistical tests. Results: Overall, ESI were recommended to 2, 022 (7.9%) patients. Patients with lumbar pain had ESI proposed 12.6% of the time. Those with cervical and thoracic symptoms had ESI recommended 3.7% and 1.8% of the time, respectively. Patients in whom ESI was recommended were more likely to have pain radiation ( P < .001), dermatomal pain distribution ( P < .001), and neurologic signs ( P < .001). They also had a greater incidence of comorbidities ( P < .001) and were older ( P < .001). There was no difference in the frequency of prior surgery ( P = .169) nor was there a difference based on gender ( P = .548) in patients not recommended to have ESI. Patients with symptom duration between 1 month and 1 year were more likely to have ESI recommended. Conclusions: ESI are commonly used to treat patients with spinal and radicular pain. There is some consistency between clinical practice and published recommendations for ESI use.